Local Government Policy in The Procurement of Rental Official Vehicle (ROV) in Keerom District, Papua - Icuk Rangga Bawono; Adhitia Pradana (Jurnal Dinamika Hukum, 2019)
The implementation of regional government requires supporting facilities and infrastructure for the smooth implementation. One of them is adequate transportation facilities. Therefore, the local government provides official vehicles for commitment and responsibility in giving attention and concern to duties of the state civil apparatus implementation. This study aims to formulate urgency of leasing operational service vehicles in the Keerom District Government. This study uses normative legal research as research method. The legal material obtained will describe and relate in such a way that it is presented in a more systematic writing to answer problems that have been formulated. Result shows the procurement of official vehicles was chosen through the rental process to minimize expenditure in the context of budget economy, effectiveness, and efficiency. Rental official vehicles in the Keerom Regency Government function as a support for regional government in achieving targets as its responsibility to provide welfare for community. Keywords: local government; operational service vehicles; rental